Recent Progress in Crystalline Borates with Edge-Sharing BO4 Tetrahedra - Li, Jing-Jing; Chen, Wei-Feng; Lan, You-Zhao; Cheng, Jian-Wen (Molecules (Basel, Switzerland), 2023)
Crystalline borates have received great attention due to their various structures and wide applications. For a long time, the corner-sharing B–O unit is considered a basic rule in borate structural chemistry. The Dy4B6O15 synthesized under high-pressure is the first oxoborate with edge-sharing [BO4] tetrahedra, while the KZnB3O6 is the first ambient pressure borate with the edge-sharing [BO4] tetrahedra. The edge-sharing connection modes greatly enrich the structural chemistry of borates and are expected to expand new applications in the future. In this review, we summarize the recent progress in crystalline borates with edge-sharing [BO4] tetrahedra. We discuss the synthesis, fundamental building blocks, structural features, and possible applications of these edge-sharing borates. Finally, we also discuss the future perspectives in this field.